Monitoring influence of urbanization on urban thermal environment using multi-temporal LANDSAT imagery: application to Da Nang city - Tu, Dang Trung; Ha, Nguyen Thi Thu; Ngan, Nguyen Thi Mai (Vietnam Journal of Earth Sciences, 2015)
This study illustrates urbanization in Da Nang city and its impacts on local thermal environments using remote sensing. In this study, multi-generation Landsat images from 1990, 1995, 2000, 2005, 2010 and 2014, were used to assess the city’s urban expansion and accompanied land surface temperature (LST) characteristics. Results showed that Da Nang urban expanded twice in 2014 (8,634 ha) comparing to 1990 (4,485 ha) and high temperature anomalies were closely associated with built-up and bare-soil land-covers. As consequence, areas covered by the highest LST correspondently expanded from center of Thanh Khe, Hai Chau districts to mostly all 6 present downtown districts. The mean LST difference between the urban downtown area and the suburban area tends to increase over time, from 7.3oC in 1990 to 11.9oC in 2014. In the context of moving towards “a friendly environmental Da Nang city”, this study  provides  useful  information  for  understanding  the  local  climatic  and  environment  changes  that  occurred  during  rapid urbanization.References An, T.T, Dieu, N.T, Minh T.P., 2011: Researching the land surface temperature in Danang city from the satellite image of Landsat 7 ETM+, National GIS Conference 2011, 14-21. Castrence, M., Nong, D.H., Tran, C.C, Young, L., Fox J., 2014: Mapping Urban Transitions Using Multi-Temporal Landsat and DMSP-OLS Night-Time Lights Imagery of the Red River Delta in Vietnam, Land 2014, 3, 148-166. Chavez Jr. P. S., 1988: An improved dark-object subtraction technique for atmospheric scattering correction of multispectral data,Remote Sensing of Environment, 24 (3): 459-479. Chen, X.L., Zhao, M.Z., Li, P.X., Yin, Z.Y., 2006: Remote sensing image-based analysis of the relationship between urban heat island and land use/cover changes, Remote Sensing of Environment, 104, 133-146. Coppin, P., Jonckheere, I., Nackaerts, K., Muys, B., Lambin, E., 2004: Digital change detection methods in ecosystem monitoring: a review,Int. J. Remote Sensing 25(9): 1565-1596. General Statistics Office, 2013: Statistical Handbook of Vietnam 2013, Statistical Publishing House. Huang, S., Taniguchi, M., Yamano, M., Wang, C., 2009: Detecting urbanization effects on surface and subsurface thermal environment - A case study of Osaka. Science of Total Environment, 407, 3142–3152. Huyen, H.T.D, Hanh L.N, 2013: Analysis of the relationship between surface temperature and buffer Danang, Journal of Science, Technology University of Da Nang, 7 (68): 31-37. Li Y-B, Shi T., Yang Y.-J., 2015: Satellite-based investigation and evaluation of the observational environment of meteorological stations in Anhui province, China, Pure Appl. Geophys., 172 (6), 1717–1733. Linh, N.H.K., Chuong H.V, 2015: Assessing the impact of urbanization on urban climate by remote sensing perspective: a case study in Danang city, Vietnam. The International Symposium on Remote Sensing of Environment, 11–15 May 2015, Berlin, Germany, 207-212. Liu, L., Zhang, Y., 2011: Urban Heat Island Analysis Using the Landsat TM Data and ASTER Data: A Case Study in Hong Kong, Remote Sens. 3, 1535-1552; doi:10.3390/rs3071535 NASA, 2012: Landsat 7 Science Data Users Handbook. 186 p (http://landsathandbook.gsfc.nasa. gov/pdfs/Landsat7_Handbook.pdf) NASA,2015: Landsat 8 Data Users Handbook. 106p (https://landsat.usgs.gov/documents/ Landsat8DataUsersHandbook.pdf) Opitz-Stapleton S., 2014: Da Nang, Vietnam: Climate Change Impacts on Heat Stress by 2050. Boulder, CO: Institute for Social and Environmental Transition-International. Qin, Z.; Zhang, M.; Amon, K; Pedro, B., 2010: Mono-window Algorithm for retrieving land surface temperature from Landsat TM 6 data, Acta Geogr. Sinica, 56, 456-466. Rodgers M.O., Stone B.J., 2001: Urban Form and Thermal Efficiency: How the Design of Cities Influences the Urban Heat Island effect, Journal of the American Planning Association, 67 (2), 186-198. Sailor, D. J., 2002: Urban Heat Islands, Opportunities and Challenges for Mitigation and Adaptation. Sample Electric Load Data for New Orleans, LA (NOPSI, 1995). North American Urban Heat Island Summit. Toronto, Canada. 1-4 May 2002. Data courtesy Entergy Corporation. Schroeder, T.A., Canty, M.J, Yang, Z., 2006: Radiometric correction of multi-temporal Landsat data for characterization of early successional forest patterns in western Oregon. Remote Sensing of Environment; 103:16-26. Shi, T., Huang, Y., Wang, H., Shi, C-E., Yang, Y-J., 2015: Influence of urbanization on the thermal environment of meteorological station: Satellite-observed evidence. Advances in Climate Change Research, 6 (1), 7-15. Smith, K.R., Woodward A., Campbell G., Lendrum D., 2014: Chapter 11. Human Health: Impacts, Adaptation, and CoGBenefits. In (Climate Change 2014: Impacts, Adaptation, and Vulnerability, Contribution of Working Group II to the Fifth Assessment Report of the IPCC, Cambridge University Press: Cambridge. Srivanit M., Hokao K., Phonekeo V., 2012: Assessing the Impact of Urbanization on Urban Thermal Environment: A Case Study of Bangkok Metropolitan, International Journal of Applied Science and Technology 2 (7): 243-256. Sun, Q.; Tan, J.; Xu, Y., 2010: An ERDAS image processing method for retrieving LST and describing urban heat evolution: A case study in the Pearl River Delta Region in South China, Environ. Earth Sci. 59, 1047-1055. Tu, D.T, Hai T.Q, Ha, N.T.T, Ngan, N.T.M, 2015: Monitoring urbanization of Da Nang city using multi-generational Landsat imagery for urban environmental planning, Journal of Environment, 8, 6-13. Van, T.T, Bao, H.D.X, 2008: A study on urban development through land surface temperature by using remote sensing: in case of Ho Chi Minh City. VNU Journal of Science, Earth Sciences 24, 160‐167. Van, T.T, Bao, H.D.X, 2010: Characteristics of Urban Thermal Environment from Satellite Remote Sensing Data in Ho Chi Minh City, Vietnam. The 1st International Electronic Conference on Remote Sensing. Yuan, F., Sawaya, K. E., Loeffelholz, B. C., & Bauer, M. E. 2005: Land cover mapping and change analysis in the Twin Cities Metropolitan Area with Landsat remote sensing, Remote Sensing of Environment, 98(2.3), 317-328. Weng Q., 2001: A remote sensing-GIS evaluation of urban expansion and its impact on surface temperature in the Zhujiang Delta, China, Int. J. Remote Sens., 22 (10), 1999-2014.